PERANG WACANA ISLAMISME DI MESIR: PERSPEKTIF LINGUISTIK - Irsyady, Kamran As'at (Universitas Islam Negeri Raden Intan Lampung, 2013)
Egypt is the ‘Mecca’ of modern Islamic thoughts. From Egypt, Islamic thoughts, both secular and traditional, have been distributed to all parts of the Islamic world. In his book, Jacob Hoigilt seeks to record and present the fierce discourse between Islamism vis-a-vis West-secularism from the perspective of linguistic disciplines. The authors conducts a critical analysis of the language (language/parole) used by Islamic thinkers in their polemic about Islamism, its meaning construction, as well as social situation underlying the polemic in Egypt. The author thoroughly scrutinizes the texts of the islamist thinkers, as well as clarifies the issues of symbolic power struggles, orthodoxy, and ideology that divide the intellectuals into liberalist and Islamist poles.